Antiviral activity of sirolimus in an HIV-positive kidney transplant recipient. (August 2019) - Alfano, Gaetano; Fontana, Francesco; Mori, Giacomo; Vicari, Emanuela; Dolci, Giovanni; Franceschini, Erica; Guaraldi, Giovanni; Mussini, Cristina; Cappelli, Gianni
Sirolimus (SIR) is a potent immunosuppressive agent with multiple proprieties. We report beneficial antiviral effects of SIR in an HIV-positive kidney transplant recipient who experienced low-level HIV-1 replication. The immunosuppressive agent was well tolerated by the patient, and no side effects were reported during follow-up. Despite immunosuppressive monotherapy, SIR ensured stable graft function.